Comportamiento agronómico de las hortalizas de hoja cilantro (Coriandrum sativum) y apio (Apium graveolens) con dos fertilizantes orgánicos en el Centro Experimental “La Playita” UTC 2013 - Amores Andrade, Ángel Gustavo (2015)
Due to the saturation of soils that are currently presented by the implementation of chemical fertilizers on crops, nowadays replacement these fertilizers with an organic product, being this beneficial to the consumer’s health. The objectives were: study of agronomic performance of leafy vegetables coriander (Coriandrum sativum) and celery (Apium graveoens), identify the best organic fertilizer for the production of leafy vegetables celery and coriander, make the economic study of treatments to study. Was applied a Design of Random Block Complete (DRBC) with four treatments and five replications for each vegetable and eight plants as experimental unit.....